Generator Listrik Tenaga Gelombang Air Menggunakan Kristal Piezoelektrik - Eko, Muhammad; Ilyas Hadikusuma, Mohd; Rusyda Saufa, Rianda (Electrical Network Systems and Sources, 2025)
This research aims to explore the utilization of water waves as a source of electrical energy using piezoelectric crystals. In this study, a device is designed to harness water waves to drive an iron marble that strikes piezoelectric crystals, generating electrical signals. The generated electrical signals are then directed to a peak detector circuit to convert the AC signal into DC, which is temporarily stored in a capacitor. This process ensures signal stability before further processing. Subsequently, the stored electrical signals in the capacitor are processed using a step-up boost converter to increase the voltage. The boosted voltage is then regulated by a charger module for efficient and safe battery charging. The generated electrical energy is stored in a battery for future use. This research aims to harness the kinetic energy from water waves and convert it into stable and well-managed electrical energy, thereby potentially supporting the development of wave-based renewable energy technology